O (log over(m, -) . log N) routing algorithm for (2 log N - 1)-stage switching networks and beyond - Chakrabarty, Amitabha; Collier, Martin J. (© 2014 Elsevier Inc., 2016)
This article was published in the Journal of Parallel and Distributed Computing [© 2014 Elsevier Inc.] and the definite version is available at :http://dx.doi.org/10.1016/j.jpdc.2014.06.004 The Journal's website is at: http://www.sciencedirect.com/science/article/pii/S0743731514001063